Jonas Cohn’s Value-Theoretical Foundation of Aesthetics - Thomas Göller (RUDN Journal of Philosophy)
Jonas Cohn (1869-1947) founded his philosophical aesthetics as a critical theory of value on the basis of the Southwest German school of Neo-Kantianism. For Cohn, aesthetic values are „purely intensive” values. As such values, they are self-sufficient values immanent to a work of art. A work of art also forms a unity of expression and design. The supra-individual value of a work of art is measured by this unity. This unity cannot be determined discursively, but is revealed individually in direct, reflection-free experience. Nevertheless, aesthetic values claim supra-individual validity. The history of art documents the ongoing debate about a general, value-based recognition of works of art. Cohn’s justification of aesthetics, which combines Kantian, neo-Kantian and life-philosophical motives, is an important contribution to a systematic justification of aesthetics despite some shortcomings. However, Cohn’s aesthetics have not yet received the attention they deserve.